Detection of orchid viruses and molecular characterization of odontoglossum ringspot virus (ORSV) isolates - R, RASHMI E; PANT, R P; B, BASAVARAJ Y; BARANWAL, V K; JAIN, RITU (The Indian Journal of Agricultural Sciences, 2025)
During a survey (2018), 44 orchid samples collected from Sikkim and Darjeeling Hills of West Bengal. The samples were examined under electron microscope (EM) followed by DAC-ELISA and RT-PCR assays were performed. Electron microscopy showed the presence of rigid rods (300 × 18 nm), flexuous rods (475 nm × 13 nm and 800 nm × 12 nm), bacilliform or bullets shaped particles (40 × 100-140 nm) and enveloped quasi-spherical particles (80-110 nm). Based on the particle morphology, DAC-ELISA was performed using the antibodies specific to odontoglossum ringspot virus (ORSV), cymbidium mosaic virus (CymMV), calanthe mild mosaic virus (CalMMV) and groundnut bud necrosis virus (GBNV), which revealed the presence of four viruses namely CymMV, ORSV, GBNV and CalMMV. RT-PCR assays also confirmed the presence of four viruses using their specific primers. The cloning, sequencing and sequence analysis of the coat protein gene sequences of the four ORSV isolates was performed. The sequence analyses revealed up to 100% sequence identity among the ORSV isolates of this study and more than 99% identity with the different ORSV isolates available at NCBI GenBank database. The higher level of sequence homology among ORSV population suggests that they are under least evolutionary pressure. The occurrence of the multiple viruses in different orchids also reflects that the orchid cultivation is under major threat.